Morphology and Genetic Diversity of Garcinia cowa (Roxb.) in Upper Brahmaputra Valley of Assam - Dutta, Mridusmita; Gogoi, Nabajyoti; Neog, Bijoy; Lekharu, Kangkana; Sonowal, Sarojmoni; Phukon, Himadree (Asian Journal of Biological and Life Sciences)
Background: Garcinia cowa is a lesser-known species and it is therefore the limelight of this study to bring to notice its morphological and genetic diversity. Materials and Methods: The morphological diversity was studied using morphological markers and the genetic diversity was analyzed using 30 different primers for ISSR analysis. The DNA isolation in 2X and 4X buffer for PCR was done using the method given by Doyle and Doyle. The method was slightly modified. Results: Tinsukia district showed the highest leaf length, leaf breadth and leaf vein. Dibrugarh district showed the highest leaf petiole. 4X buffer proved to be more effective lysis buffer in comparision to 2X buffer. Garcinia cowa showed 100% polymorphism with primers UBC-41 and UBC-42. Conclusion: Garcinia cowa was found to have considerable morphological diversity. 4X buffer proved to be more effective. The accessions of Garcinia cowa showed polymorphism only with primers UBC-40, UBC-41 and UBC-42 and the polymorphism percentage of Garcinia cowa was calculated which was found to be 100% with primers UBC-41 and UBC-42.
Keywords: Garcinia cowa; ISSR; Morphological diversity; PCR